Changing Health Care Professionals' Attitudes Toward Spanking. (October 2016) - Burkhart, Kimberly; Knox, Michele; Hunter, Kimberly
Twenty-two pediatric residents and 31 medical students viewed the Play Nicely program. The Play Nicely program is a multimedia program that teaches health care professionals how to counsel parents to use positive parenting and disciplining strategies in response to early childhood aggression. Health care professionals completed pre- and posttraining questionnaires to assess changes in comfort with counseling, parenting knowledge, and attitudes toward spanking. Results indicated at posttraining that health care professionals were significantly more comfortable with counseling parents, had increased parenting knowledge, and decreased positive attitudes toward spanking. Findings suggest that this program holds promise for educating health care professionals on how to counsel parents on positive parenting strategies and positively change attitudes toward spanking.